Age and ergonomic position as determinants of musculoskeletal disorders among Batik workers: A cross-sectional study - Arif Pristianto; Adnan Faris Naufal; Mahendra Wahyu Dewangga; Rita Setiyaningsih; Wulan Adis Aranti; Ana Triasari; Mutiara Sabta Amanda; Nabila Rizka Lathifani; Azizah Shalsa Billa; Samiyem Samiyem; Muhammad Nizar Siddiq (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Musculoskeletal disorders (MSDs) are complaints that occur in human muscles and bones, which are caused by several factors such as excessive work, lifting heavy loads, age, gender, and others. This study aimed to analyze the relationship between age and ergonomic working positions with the occurrence of MSDs across different divisions and types of batik production. Methods: This study used a cross-sectional design with cross-divisional analysis based on the type of batik worked on. The study involving 60 respondents selected through purposive sampling from Laweyan Batik Village. Research data was collected using several instruments, including: Nordic body map (NBM), Oswestry disability index (ODI), work ergonomic risk assessment (WERA), and numeric rating scale (NRS). Results: It was found that age was not related to the cause of changes in waist functional ability, with p-value= 0.342. There is a relationship between the level of waist ergonomics when working and the risk of lower back pain in batik makers, with p-value= 0.030. Conclusion: There is a relationship between the level of waist ergonomics when working and the risk of lower back pain in batik makers, but age was not related with musculoskeletal disorders in batik workers.